The interpretation of overt subject pronominals in Turkish - Oktay ÇINAR (Dilbilim Araştırmaları Dergisi)
This study explores the interpretation of co-indexation between overt subject pronominals, specifically o and kendisi, with quantified/wh-word antecedents among native Turkish speakers. The research employs a task designed to elicit responses that either force a bound or disjoint interpretation within biased contexts. The findings reveal that o and kendisi are not interchangeable within the same context. A closer examination unveils that the interpretation of o is governed by certain syntactic constraints, although target-deviant interpretations are observed. In contrast, kendisi is more likely to be interpreted as a bound pronoun, even though both bound and disjoint interpretations are syntactically accessible. This shows that the constraint governing the binding of overt subject pronominals to quantified/wh-word antecedents, known as the Overt Pronoun Constraint, is operative for o but not for kendisi. The distinction in the behavior of these pronominals can be attributed to the diffrences in their syntactic configurations: o is costly configured than kendisi, hence displaying asymmetry across quantified/wh-word antecedents. Since the binding relations of kendisi is similar to pro, it is more prone to binding by the matrix subject.